Molecular and metabolic insights into floral scent biosynthesis during flowering in Dendrobium chrysotoxum - Du, Zhihui; Jin, Yuxuan; Wang, Weize; Xia, Kuaifei; Chen, Zhilin (Frontiers in Plant Science, 2022)
Dendrobium chrysotoxum is considered as an important ornamental dendrobium because of its strong and long-lasting floral scent. Nevertheless, few information is known about the dynamic changes and related formation mechanism of dendrobium floral scent at different flowering stages. In this study, the characteristics and biosynthetic mechanism of floral scent in D. chrysotoxum during flowering was revealed by using widely-targeted volatilomics (WTV) combined with transcriptome analysis. Over 500 kinds of volatile organic compounds (VOCs) were detected in the floral scents of D. chrysotoxum, which improved the knowledge about floral scent components of dendrobium. A total of 153 differential VOCs and 4,487 differentially expressed genes (DEGs) were identified between flowers of different flowering stages, respectively. The results for both volatilomics and transcriptomics data indicated that terpenes and related genes played an important role in the formation of floral characteristics of D. chrysotoxum. But in general, the expression of genes showed an opposite trend to the accumulation of metabolites during flowering, suggesting that the regulation of floral scent biosynthesis might have started at the budding stage in D. chrysotoxum. Additionally, a transcriptional metabolic regulatory network consisting of terpenes, terpene synthases and candidate transcription factors was established. This research is the first systematic and comprehensive exploration of floral characteristics and related mechanisms during flowering in D. chrysotoxum. It provides basis for exploration of mechanisms on the floral scents and the breeding of aromatic dendrobium.